2021
DOI: 10.2147/dddt.s310820
|View full text |Cite
|
Sign up to set email alerts
|

Novel Phenolic Compounds as Potential Dual EGFR and COX-2 Inhibitors: Design, Semisynthesis, in vitro Biological Evaluation and in silico Insights

Abstract: Introduction Epidermal growth factor receptor (EGFR) inhibition is an imperative therapeutic approach targeting various types of cancer including colorectal, lung, breast, and pancreatic cancer types. Moreover, cyclooxygenase-2 (COX-2) is frequently overexpressed in different types of cancers and has a role in the promotion of malignancy, apoptosis inhibition, and metastasis of tumor cells. Combination therapy has been emerged to improve the therapeutic benefit against cancer and curb intrinsic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…43,[45][46][47] COX-2 is an enzyme that plays an important role in inflammatory responses through PGE2 synthesis from arachidonic acid, and it is selectively overexpressed in colon tumors. 43,48,49 Hence, COX-2 selective pharmacological inhibition may reduce the incidence of CRC. According to the American Cancer Society, there is a high prevalence of CRC in IBD patients, and p-CouA alleviates DSS-induced intestinal inflammation by suppressing the expression of COX-2.…”
Section: Modulating Inflammationmentioning
confidence: 99%
“…43,[45][46][47] COX-2 is an enzyme that plays an important role in inflammatory responses through PGE2 synthesis from arachidonic acid, and it is selectively overexpressed in colon tumors. 43,48,49 Hence, COX-2 selective pharmacological inhibition may reduce the incidence of CRC. According to the American Cancer Society, there is a high prevalence of CRC in IBD patients, and p-CouA alleviates DSS-induced intestinal inflammation by suppressing the expression of COX-2.…”
Section: Modulating Inflammationmentioning
confidence: 99%
“…As previously reported, the standard kinase screening protocol was used (Table 2). Further details are explained in the Supplementary Materials [34,35].…”
Section: Egfr Inhibitory Activitymentioning
confidence: 99%
“…Abou-Zied HA et al designed a novel xanthine derivative carrying the chalcone component to investigate potential EGFR inhibitors, and obtained the compound 11 against the target enzyme with IC 50 = 0.3 µM [21]. Abdelgawad et al designed novel phenolic compounds as potential inhibitors of EGFR and COX-2, and obtained the compounds C4 and G4 with IC 50 of 0.9 and 0.5 µM, respectively [22]. N Nerdy et al found that sesquiterpene lactones from veronica amygdaline de le had anticarcinogenic potential by inhibiting the EGFR expression [23].…”
Section: Introductionmentioning
confidence: 99%